2013
DOI: 10.15835/nsb539080
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Profile and Microbial Diversity During Bioconversion of Sugarcane Press Mud Using Bacterial Suspension

Abstract: This study was aimed at investigating the physico-chemical and microbial diversity for rapid composting of sugarcane press mud (PM) leading to organic manure. Five bacterial strains (Cellulomonas sp., Klebsiella sp., Proteus sp., Enterobacter sp., Salmonella sp.) were tested under in vivo conditions for bioconversion of PM using pile method. Results revealed that combined inoculation of bacterial consortia was found to be the best decomposer of PM resulting reduction of organic carbon content (26.75%), C:N rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The shift of pH towards normal is the indication of maturity of compost. The present results are in conformity with the results of research workers who revealed from their studies that the organic matter decomposes gradually with time, stabilizes with final pH of compost between 7 to 8 with reduction in C: N ratio (Ranalli et al, 2001, Gade et al, 2010Raj and Antil, 2011;Himanen and Hanninen, 2011;Sarker et al, 2013).…”
Section: Changes In Ph and C: N Ratiosupporting
confidence: 93%
See 1 more Smart Citation
“…The shift of pH towards normal is the indication of maturity of compost. The present results are in conformity with the results of research workers who revealed from their studies that the organic matter decomposes gradually with time, stabilizes with final pH of compost between 7 to 8 with reduction in C: N ratio (Ranalli et al, 2001, Gade et al, 2010Raj and Antil, 2011;Himanen and Hanninen, 2011;Sarker et al, 2013).…”
Section: Changes In Ph and C: N Ratiosupporting
confidence: 93%
“…Several research workers estimated the nutrient value of compost prepared on inoculation with microbes over the uninoculated control. Patil (1994), Verma et al, (1999) and Sarker et al, (2013) revealed that the compost prepared on inoculation of microbes showed the better nutrient levels compared to uninoculated control. This is probably because of quick microbial activity leading to decrease in volume of the material.…”
Section: Mineral Components Of Compost At Maturitymentioning
confidence: 99%
“…Data presented in table-I stated that the total phosphorus content revealed an increasing value from 2.31% to 3.96% in raw and composted groundnut shell and vegetable waste. The present study indicates an increase in total phosphorus content during composting of press mud using bacterial consortium from 0.58% to 1.46% with an incubation period of 49 days 24 .…”
Section: Physicochemical Properties Of Raw and Composted Vegetables Amentioning
confidence: 52%
“…In parallel, it increased the nitrogen (2.34%), phosphorus (1.15%), and potassium (1.37%) content along with the population of microorganisms i.e., bacteria, fungi, and actinomycetes. 85…”
Section: Agro-industrial Wastepotato and Sugarcanementioning
confidence: 99%